A New Concept in Picosecond Lasers: New solutions successfully demonstrated within BMBF joint project iPLASE. Issue 1 (21st January 2016) - Hohmuth, Rico; Burdack, Peer; Limpert, Jens
Abstract: Over the last decade, mode‐locked laser sources in the ten picosecond pulse regime expanded into medical applications and high‐precision micro‐material machining. However, the complexity and the alignment sensitivity of picosecond lasers translated to higher cost and impeded a broader market entry. The goal of the iPLASE project was to develop a novel laser concept (Fig. 1) which is capable of generating sub‐10 picosecond pulses. To this end, we shortened the pulses of a novel amplified microchip laser using a pulse compressor. This article outlines the key achievements of the project.